Analisis Faktor yang Menyebabkan Belum Tercapainya Target Pelaporan Nilai Kritis Laboratorium: Studi di Instalasi Patologi Klinik Rumah Sakit Umum Haji Surabaya - Sonny Marsetyo (Media Gizi Kesmas, 2023)
Background: A laboratory critical value is a laboratory test result represents a pathophysiologic state at such variance with normal which threaten patient's life if a medical action is not taken immediately and for which an effective action is possible. The reporting of laboratory critical value at the Clinical Pathology Department at Haji General Hospital Surabaya for the January-July 2020 period had not reached 100%. Objectives: This study analyzed the factors cause the target of laboratory critical value report has not been reached at the Clinical Pathology Department at Haji General Hospital Surabaya based on psychological and organizational factors. Methods: This study was a descriptive observational study with cross-sectional approach. The samples were 23 people in total sampling. The data were collected by questionnaire that had been tested for validity and reliability. Results: The results showed that 73.9% of respondents had high motivation, 91.3% of respondents had good perceptions, 82.6% of respondents had type B personality, 69.6% of respondents had good learning, 78.3% respondents had low work stress, 52.2% of respondents stated that leadership was quite good, 95.7% of respondents said moderate rewards, 60.9% of respondents stated that the work design was according to the profession, 87.0% of the organizational structure was effective. Conclusion: Factors that caused target of laboratory critical value report has not been reached at the Clinical Pathology Department at Haji General Hospital Surabaya for the January-July 2020 period, based on the 80/20 Pareto Principle are motivation, learning, leadership, and job design. Health analysts should increase self-motivation, make experiences as learning, leaders as co-workers, work well willingly and the Clinical Pathology Department to reward the best employees, conduct evaluations, provide understanding and explanation in decision making, regulate the rotation of the division of tasks.